PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PAKET WISATA DI PT. NUSA DEVATA BALI HOLIDAY - Nurul Hakiki Nurul Hakiki; I Nengah Subadra; Ni Putu Yunik Anggreni (Universitas Triatma Mulya, 2021)
This research to analyze the effect to price and quality product on buying decision of tour package partially and simultanly. The sample used in this study is purposive sampling technique where use 98 respondens of all the domestic tourist. The analysis technique used in this study are analysis descriptive, analysis classic assumption, correlation analysis, analysis regression multiple linear, hypothesis testing (T-test and F-test), analysis of determination, and analysis standardized coefficients beta. The results of this research are analysis show that price (X1) partially has a positive and significant effect on buying decision of tour package at PT. Nusa Devata Bali Holiday Bali which is shown by the positive coefficient of b1x1 regression. Quality product (X2) has a positive and significant effect on buying decision of tour package at PT. Nusa Devata Bali Holiday Bali, this can be seen from the regression coefficient b2x2 which is positive. Other information obtained is that price (X1) and quality product (X2) has a positive and significant influence on buying decision of tour package (Y) at PT. Nusa Devata Bali Holiday Bali, this is confirmed by using the F test obtained F count = 14,429> F table = 3.092 with Sig.F = 0,000 (p <0.05). The amount of influence contributed by price (X1) and quality product (X2) on buying decision (Y) is 23.3%, while the remaining 76.7% is influenced by other variables outside of this observation.